Interleukin 8 receptor deficiency confers susceptibility to acute experimental pyelonephritis and may have a human counterpart - Frendeus, Björn; Godaly, Gabriela ; 0000-0002-3467-1350; Hang, Long; Karpman, Diana ; 0000-0001-7220-7658; Lundstedt, Ann-Charlotte; Svanborg, Catharina (Journal of Experimental Medicine, 2000)
Neutrophils migrate to infected mucosal sites that they protect against invading pathogens. Their interaction with the epithelial barrier is controlled by CXC chemokines and by their receptors. This study examined the change in susceptibility to urinary tract infection (UTI) after deletion of the murine interleukin 8 receptor homologue (mIL-8Rh). Experimental UTIs in control mice stimulated an epithelial chemokine response and increased chemokine receptor expression. Neutrophils migrated through the tissues to the epithelial barrier that they crossed into the lumen, and the mice developed pyuria. In mIL-8Rh knockout (KO) mice, the chemokine response was intact, but the epithelial cells failed to express IL-8R, and neutrophils accumulated in the tissues. The KO mice were unable to clear bacteria from kidneys and bladders and developed bacteremia and symptoms of systemic disease, but control mice were fully resistant to infection. The experimental UTI model demonstrated that IL-8R-dependent mechanisms control the urinary tract defense, and that neutrophils are essential host effector cells. Patients prone to acute pyelonephritis also showed low CXC chemokine receptor 1 expression compared with age-matched controls, suggesting that chemokine receptor expression may also influence the susceptibility to UTIs in humans. The results provide a first molecular clue to disease susceptibility of patients prone to acute pyelonephritis.
Keywords: chemokine receptor; urinary tract infection; knockout mice; mucosal immunity; lipopolysaccharide